2019
DOI: 10.1021/acs.jpcc.9b01369
|View full text |Cite
|
Sign up to set email alerts
|

Light Scattering, Absorption, and Refraction due to High-Order Optical Nonlinearities in Colloidal Gold Nanorods

Abstract: We investigated the nonlinear (NL) optical behavior of aqueous colloidal dispersions of rod-shaped gold nanoparticles (NPs) with different aspect ratios beyond the usual analysis of third-order nonlinearity. By applying the Z-scan technique, it was possible to observe large NL absorption, which is understood by considering the simultaneous instantaneous and thermo-optical nonlinearity contributions. In addition, light-scattering experiments were performed at high intensities, showing a significant contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 74 publications
1
22
0
Order By: Relevance
“…The broad absorption band peaked at ≈378 nm corresponds to the transverse dipolar LSP resonance of Ag NWs, while the small shoulder around 350 nm is attributed to the transverse quadrupole resonance. 30 The longitudinal resonance band, which is commonly observed at longer wavelengths for rod-shaped nanoparticles, 31 appears as a broad band in the spectrum, rather than a resonance peak, due to the long length of Ag NWs.…”
Section: Resultsmentioning
confidence: 99%
“…The broad absorption band peaked at ≈378 nm corresponds to the transverse dipolar LSP resonance of Ag NWs, while the small shoulder around 350 nm is attributed to the transverse quadrupole resonance. 30 The longitudinal resonance band, which is commonly observed at longer wavelengths for rod-shaped nanoparticles, 31 appears as a broad band in the spectrum, rather than a resonance peak, due to the long length of Ag NWs.…”
Section: Resultsmentioning
confidence: 99%
“…Notice that the scattered intensity starts to deviate from a linear response at around 75 GW/cm 2 . We recall that NLS can play a role in the optical nonlinearity of nanoscatters, leading to, for example, an optical limiting behavior in LTMDs …”
Section: Discussionmentioning
confidence: 99%
“…29 With the same nonlinearity management procedure, it was reported that besides the third-order nonlinearity the quintic nonlinearity also plays an important role in the nonlinear refractive behavior of Au-NR colloids, being able to change its nonlinear behavior from self-focusing to self-defocusing, for intensities larger than 1 GW/cm 2 . 29 In addition, the variations of the fifth-order refractive index were associated with a quintic scattering phenomenon, which can be modified by managing the volume fraction and nanorod aspect ratio. 29 Figure 3 illustrates the spectral behavior of the light emitted by a sample consisting of Au-NRs, with AR = 1.8, suspended in an ethanol−Rh 6G solution.…”
Section: Resultsmentioning
confidence: 99%